Making the European polity : reflexive integration in the EU - Eriksen, Erik Oddvar, 1955- (Routledge studies on democratizing Europe ;, 2005)
Today's Europe is marked by an amazing pace of integration. The European Union now consists of twenty five member states, however there is confusion and disagreement about its future design. Making The European Polity investigates how the European Union should develop and organize itself and offers a reflexive approach to integration based on the theory of communicative action. It conceives of the EU as a law based supranational polity lacking the identity of a people as well as the coercive means of a state and argues that it is a polity with an organized capacity to act, but no sole apex of.